(Plant Community Composition Under Mature Oil Palm Stands) - Asbur, Yenni; Purwaningrum, Yayuk (Jurnal Penelitian Kelapa Sawit, 2024)
The composition of vegetation under a tree stand reflects the impact of environmental features such as spontaneous cover of undergrowth in tree stand aisles and is a soil conservation method that is often used and has several benefits, such as reducing erosion, increasing nutrient retention after rain, increasing carbon content soil and other nutrients. The aim of this research is to identify the composition of plant communities and determine the dominant plant species. The research was carried out in a 15 years old smallholder oil palm plantation in Naga Rejo Village, Galang District, Deli Serdang, North Sumatra. Identification of plant community composition under oil palm stands was carried out using the 1 m x 1 m quadrat method. The dominant plant species under oil palm stands is A. trapeziformis from the fern type, followed by A. gangetica from the broadleaf type, P. ensiformis from the fern type, C. acrescens from the grass type, and N. biserrata from the fern type with index its species diversity is classified as moderate (H’ = 2.03).